Adiabatic shear instability is not necessary for adhesion in cold spray. (1st October 2018) - Hassani-Gangaraj, Mostafa; Veysset, David; Champagne, Victor K.; Nelson, Keith A.; Schuh, Christopher A.
Abstract: When metallic microparticles impact substrates at high enough velocity, they bond cohesively. It has been widely argued that this critical adhesion velocity is associated with the impact velocity required to induce adiabatic shear instability. Here, we argue that the large interfacial strain needed to achieve bonding does not necessarily require adiabatic shear instability to trigger. Instead, we suggest that the interaction of strong pressure waves with the free surface at the particle edges—a natural dynamic effect of a sufficiently rapid impact—can cause hydrodynamic plasticity that effects bonding, without requiring shear instability. We proceed on this basis to postulate and confirm a proportionality between critical velocity and the bulk speed of sound, which supports the viewpoint that shear instability is not the mechanism of adhesion in cold spray. Graphical abstract: Image 1